2001
DOI: 10.1111/j.1749-6632.2001.tb03524.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Fibrin with VE‐Cadherin

Abstract: The conversion of fibrinogen into fibrin and the association of fibrin(ogen) with activated platelets play a fundamental role in hemostasis because their interaction with the injured vessel prevents blood extravasation. Platelet aggregates and fibrin also participate in the occlusion of the vascular lumen in pathological conditions. Fibrin II also promotes the formation of new blood vessels, for example, during wound healing and tumor growth. Using an in vitro assay, we have studied the mechanism by which fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 38 publications
3
79
1
Order By: Relevance
“…First, the N-terminal portions of fibrin ␤ chains (amino-acid residues ␤15-42), which are exposed after cleavage of FpB, have been implicated in a number of important processes, including angiogenesis and inflammation. [39][40][41][42][43][44][45][46][47][48] Second, the released FpB is a potent chemoattractant, 42 and therefore its preferential release may indicate the physiological purpose in the attraction of cells to the site of injury.It has been shown that the association of soluble fibrinogen with the fibrin clot results in the reduced adhesiveness of such fibrinogenfibrin matrices toward leukocytes and platelets. 49,50 Our finding that FpA is less accessible for thrombin in surface-bound fibrinogenfibrin complexes may be interpreted as a novel supplementary mechanism preventing the rapid conversion of bound fibrinogen into fibrin, thereby extending its anti-adhesive properties and providing an additional level of protection of thrombi from premature dissolution.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…First, the N-terminal portions of fibrin ␤ chains (amino-acid residues ␤15-42), which are exposed after cleavage of FpB, have been implicated in a number of important processes, including angiogenesis and inflammation. [39][40][41][42][43][44][45][46][47][48] Second, the released FpB is a potent chemoattractant, 42 and therefore its preferential release may indicate the physiological purpose in the attraction of cells to the site of injury.It has been shown that the association of soluble fibrinogen with the fibrin clot results in the reduced adhesiveness of such fibrinogenfibrin matrices toward leukocytes and platelets. 49,50 Our finding that FpA is less accessible for thrombin in surface-bound fibrinogenfibrin complexes may be interpreted as a novel supplementary mechanism preventing the rapid conversion of bound fibrinogen into fibrin, thereby extending its anti-adhesive properties and providing an additional level of protection of thrombi from premature dissolution.…”
mentioning
confidence: 99%
“…First, the N-terminal portions of fibrin ␤ chains (amino-acid residues ␤15-42), which are exposed after cleavage of FpB, have been implicated in a number of important processes, including angiogenesis and inflammation. [39][40][41][42][43][44][45][46][47][48] Second, the released FpB is a potent chemoattractant, 42 and therefore its preferential release may indicate the physiological purpose in the attraction of cells to the site of injury.…”
mentioning
confidence: 99%
“…Fibrinogen also plays a role in the initiation of angiogenesis (Chalupowicz et. al., 1995;Martinez et. al., 2001), and the propagation of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the innate immune response is activated to defend the host against this neoplastic insult. Release of IL-6 systemically leads to increased production of plasma Fg and fibrin formation resulting in exposure of  15-42 and binding to VE-cadherin, a step critical for angiogenesis (Bach et al, 1998b;Martinez et al, 2001). Furthermore, VEGF binds to Fg and fibrin with high affinity (Sahni & Francis, 2000), which may be necessary for Fg to enhance VEGF-mediated endothelial cell permeability without potentiating endothelial cell proliferation.…”
Section: Wwwintechopencommentioning
confidence: 99%